The paradox of freedom: Determinism, Free Will and Responsibility - Kokko, Ville V. (fi=Turun yliopisto|en=University of Turku|, 2025)
This dissertation examines the question of how we should understand free will and moral responsibility. The traditional approaches to the question have often concerned the compatibility of freedom and responsibility with determinism and indeterminism. Determinism implies that given the present, only one future is possible, which means that human choices, also, are “determined in advance” in some sense. Meanwhile, if a choice is indeterministic, it seems to be partly out of the agent’s control. Thus, both options seem problematic for both freedom and responsibility. I start my study by examining this problem but then move beyond it to examine the connection between free will and moral responsibility before formulating my own proposition for how both concepts are best understood. I begin my study of the relationship between (in)determinism and free will by making clear which definition of (in)determinism I use in this work. One key point is how these concepts are always tied to a given level of description; the universe being (in)deterministic at the bottom does not equate it to being so on some higher level, such as that of human choices. I go on to present my own carefully formulated version of what I call the randomness argument. This consists of two related claims. First, indeterminism in choices contradicts a person’s control over the in a specific sense, insofar as it has any effect. Second, there is no reason to want free will to be indeterministic that is not reducible to a bare intuition that it must be. I examine numerous objections and theories that could counter this argument and show that none of them do. Next, I go on to argue that we have mixed intuitions about whether free will should be indeterministic or deterministic. However, since I argued there is no reason to want indeterminism other than such intuitions, I also argue that we will do best to adopt a compatibilist view of free will, in which it is compatible with determinism. However, I go on to examine why it might be that we have incompatibilist intuitions in the first place to see what exactly we should understand free will as involving. I argue that most forms of determinism indeed contradict free will, and what emerges as a suitable criterion for free will is reasons-responsiveness. After examining free will, I turn to the concept of moral responsibility. I examine the common assumptions made about how moral responsibility is connected to free will on the one hand and differential treatment such as punishment on the other. I argue that none of these connections can be justified by intuition. However, instead of rejecting them, I argue that they can be justified by building on my model of freedom as involving reasons-responsiveness. If the fundamental purpose of holding responsible is to guide behaviour, it makes sense to limit this to cases where the person is responsive to reasons. I also show that this model can explain and justify a number of things about how we actually hold people responsible. In the conclusion, I show how my model presents a unified, reasoned basis for justifying the ethics of moral responsibility and their connection to free will. Free will is explained as the ability to act on one’s best reasons, whereas responsibility is based on the ability to make a difference. Two important challenges we must face are that we are not fully free in this sense – but can become more so – and that there is no principle that can always tell us when to assign responsibility.

Tämä väitöskirja tarkastelee kysymystä siitä, miten meidän tulisi ymmärtää vapaa tahto ja moraalinen vastuu. Perinteisesti on yleensä kysytty, sopivatko vapaus ja vastuu yhteen determinismin ja indeterminismin kanssa. Determinismistä seuraa, että jos nykyhetki on kiinnitetty, vain yksi tulevaisuus on mahdollinen. Tämä tarkoittaa, että myös ihmisten valinnat ovat ”etukäteen määrättyjä”. Jos taas valinta on indeterministinen, se näyttää olevan osittain hallitsematon. Täten molemmat vaihtoehdot näyttävät ongelmallisilta vapaudelle ja vastuulle. Aloitan tämän tutkimuksen tarkastelemalla tätä ongelmakenttää, mutta sitten siirryn siitä eteenpäin ja tutkin yhteyttä vapaan tahdon ja moraalisen vastuun välillä. Lopuksi muotoilen oman ehdotukseni sille, miten molemmat käsitteet tulisi ymmärtää. Aloitan tutkimukseni (in)determinismin ja vapaan tahdon suhteesta selventämällä, mitä (in)determinismin määritelmää käytän tässä työssä. Yksi keskeinen havaintoni on se, että nämä käsitteet ovat aina sidottuja tiettyyn kuvauksen tasoon. Se, että maailma on (in)deterministinen syvimmällä tasolla ei tarkoita, että se olisi samanlainen jollakin toisella tasolla, kuten ihmisen valinnan tasolla. Jatkan tästä esittämällä huolellisesti muotoillun version argumentista, jota itse kutsun satunnaisuusargumentiksi. Se koostuu kahdesta toisiinsa liittyvästä väitteestä. Ensiksi indeterminismi valinnoissa on ristiriidassa valitsijan hallinnan kanssa tietyssä määrittelemässäni mielessä sikäli kuin sillä on mitään vaikutusta. Toiseksi ei ole mitään syytä haluta vapaan tahdon olevan indeterminististä, paitsi sellaisia, jotka palautuvat intuitioon siitä, että näin on oltava. Tarkastelen lukuisia vastaväitteitä ja teorioita, jotka voisivat kumota nämä väitteen, ja näytän, ettei yksikään niistä onnistu siinä. Seuraavaksi argumentoin, että meillä on ristiriitaisia intuitioita sen suhteen, onko vapaa tahto indeterminististä vai determinististä. Koska ainoa syy haluta indeterminismiä ovat intuitiot, väitän, että on parasta omaksua kompatibilistinen näkemys tahdonvapaudesta, jonka mukaan determinismi on sen kanssa yhteensopivaa. Tästä jatkan kuitenkin tarkastelemalla sitä, mitä inkompatibilistiset intuitiomme paljastavat siitä, miten vapaa tahto tulisi ymmärtää. Argumentoin, että useimmat determinismin muodot ovatkin ristiriidassa tahdonvapauden kanssa, ja sopivaksi kriteerille tahdonvapaudelle paljastuu perusteherkkyys. Tarkasteltuani tahdonvapautta siirryn käsittelemään moraalisen vastuun käsitettä. Tarkastelen yleisiä oletuksia siitä, miten vastuu liittyy yhtäältä tahdonvapauteen ja toisaalta ihmisten eriarvoiseen kohteluun, kuten rankaisemiseen. Väitän, että mitään näistä yhteyksistä ei ole riittävää perustella intuitioihin vetoamalla. En kuitenkaan hylkää niitä, vaan argumentoin, että ne voidaan oikeuttaa laajentamalla malliani, jossa vapaus liittyy perusteherkkyyteen. Jos vastuussa pitämisen perimmäinen tarkoitus on ohjata ihmisten käytöstä, on syytä rajoittaa tämä sellaisiin tapauksiin, joissa ihminen pystyy reagoimaan perusteisiin. Osoitan myös, että tämä malli pystyy selittämään ja oikeuttamaan monia puolia siitä, miten käytännössä pidämme ihmisiä vastuussa. Johtopäätöksessäni osoitan, miten esittämäni malli antaa yhtenäisen, perustellun oikeutuksen moraalisen vastuun etiikalle sekä sen yhteydelle tahdonvapauteen. Tahdonvapaus selitetään kykynä toimia omien parhaiden syiden mukaan, kun taas vastuu perustuu mahdollisuuteen vaikuttaa asioihin. Kaksi tärkeää haastetta ihmiselle ovat, että emme ole täysin vapaita tässä mielessä – vaikka voimme tulla paremmiksi – ja se, että ei ole mitään lopullista periaatetta, joka voi aina kertoa, ketä pitää vastuussa.